Secure Dynamic Resource Provisioning Cost by Optimized Placement of Virtual Machines in Cloud Computing - S, Aarthee; R, Venkatesan (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Cloud computing provides pay-as-you-go computing resources and accessing services are offered from data centers all over the world as the cloud. Consumers may find that cloud computing allows them to reduce the cost of information management as they are not required to own their servers and can use capacity leased from third parties or cloud service providers. Cloud consumers can successfully reduce total cost of resource provisioning using Optimal Cloud Resource Provisioning (OCRP) algorithm in cloud computing environment. The two provisioning plans are reservation and on-demand, used for computing resources which is offered by cloud providers to cloud consumers. The cost of utilizing computing resources provisioned by reservation plan is cheaper than that provisioned by on-demand plan, since a cloud consumer has to pay to provider in advance. This project proposes that the OCRP algorithm associated with rule based resource manager technique is used to increase the scalability of cloud on-demand services by dynamic placement of virtual machines to reduce the cost and also endow with secure accessing of resources from data centers and parameters like virtualized platforms, data or service management are monitored in the cloud environment.